The Role Of Islamic Banks In Improving The Indonesian Economy - Tiffani, Tiffani; Martin Kustati; Nana Sepriyanti; Nurhasnah, Nurhasnah; Wahyu Hidayat; Mardianto, Mardianto (Cita konsultindo, 2024)
Islamic banks are banks that operate on sharia principles or Islamic law, this principle has been applied since the time of Rasullah, khulafaur Rasyidan, caliphs to modern times. The main principles of Islamic banking include the prohibition of usury (interest), the prohibition of investing in businesses that are prohibited by Islam. This research method is designed with a qualitative approach because the results obtained are not in the form of numbers. The selection of a qualitative approach in this text was chosen because it is more in line with the scope of the discussion under study. The use of qualitative data is intended to ensure that the information obtained can be presented naturally and authentically. Desk research where the research is conducted without the researcher being directly involved in the field. The results of the study identify sharia principles such as the prohibition of usury, profit sharing (Mudharabah and Musyarakah), prohibition of risky or illegal transactions, transparency and openness, fairness and reasonableness, finally community and common interests are well implemented and lead to positive trends based on the results of literature study research from previous researchers In Indonesia, for example, the Islamic banking industry has experienced significant growth. In recent years, the number of Islamic banks has continued to grow, both in terms of number and size of operations. The increasing assets, loans, and deposits in Indonesian Islamic banks indicate that people are increasingly interested in financial products and services that comply with sharia principles. Islamic banks play an important role in the Indonesian economy in several ways: increased access to finance, diversification of products and services, financial sector growth, equality and fairness,kContribution to financial system stability.